2004
DOI: 10.1086/422040
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response of Patients with Severe Acute Respiratory Syndrome (SARS) Targets the Viral Nucleocapsid

Abstract: The recent outbreak of severe acute respiratory syndrome (SARS) provided an opportunity to study the antibody response of infected individuals to the causative virus, SARS coronavirus. We examined serum samples obtained from 46 patients with SARS, 40 patients with non-SARS pneumonia, and 38 healthy individuals, by use of Western blotting (WB), enzyme-linked immunoassay (ELISA), and immunofluorescence assay, using both native and bacterially produced antigens of the virus. We found a highly restricted, immunogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
216
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(230 citation statements)
references
References 23 publications
14
216
0
Order By: Relevance
“…2A Right). These results are consistent with previous studies that identified the N proteins of coronaviruses as the most abundant and reactive antigens (11).…”
Section: Serum Probing Of the Coronavirus Proteome Microarray With Humansupporting
confidence: 93%
See 1 more Smart Citation
“…2A Right). These results are consistent with previous studies that identified the N proteins of coronaviruses as the most abundant and reactive antigens (11).…”
Section: Serum Probing Of the Coronavirus Proteome Microarray With Humansupporting
confidence: 93%
“…However, it is not useful once the infection is cleared and can be challenging to implement in clinical application; the collection of samples such as nasopharyngeal or bronchial alveolar aspirates from SARS patients is dangerous and can put healthcare workers at high risk. ELISAs tend not to be highly sensitive and usually require large amounts of sample (8)(9)(10)(11). Moreover, existing ELISAs, such as one manufactured by Euroimmun (Luebeck, Germany), use whole viral extracts, thereby increasing the chance of misdiagnosis due to crossreactivity with proteins from other viruses.…”
mentioning
confidence: 99%
“…Anti-N antibodies were present at high levels in SARS patients and persisted for a long time. In agreement, vectors that expressed full-length or truncated N proteins were highly immunogenic Guan et al, 2004;Huang et al, 2004;Leung et al, 2004;Tan et al, 2004;Woo et al, 2004). Hence, the S and N proteins may be the most promising vaccine candidates against SARS-CoV.…”
Section: Discussionmentioning
confidence: 64%
“…Subunit vaccines containing HLA-A*0201 restricted peptides is highly effective for the induction of strong cytotoxic T-cell response against infectious virus [6]. Among the four structure proteins of the SARS-CoV, the S and N proteins are the major targets for vaccine research studies due to their potency in triggering immune responses [7][8][9][10][11][12][13][14]. The S protein contains 1256 amino acids and is involved in viral entry through angiotensin-converting enzyme 2 receptor on host cell surface [15,16] and the N protein contains 422 amino acids and is involved in the viral RNA packaging [17,18].…”
Section: Introductionmentioning
confidence: 99%